Implications of hydrodynamic testing to guide sizing of self‐expanding transcatheter heart valves for valve‐in‐valve procedures. Issue 3 (24th October 2019) - Sathananthan, Janarthanan; Hensey, Mark; Fraser, Rob; Landes, Uri; Blanke, Philipp; Hatoum, Hoda; Dasi, Lakshmi Prasad; Sedaghat, Alexander; Bapat, Vinayak N; Leipsic, Jonathon; Søndergaard, Lars; Wood, David A.; et al.
Abstract: Aims: The commonly used valve‐in‐valve (VIV) app recommends sizing based on dimensions of both the transcatheter heart valve (THV) and bioprosthetic surgical valve. The implications of hydrodynamic testing to guide VIV sizing are poorly understood. This bench study assessed the hydrodynamic performance of different sizes of self‐expanding supra‐annular THVs in three different surgical aortic bioprostheses at different implantation depths. Methods: A small versus medium ACURATE neo (ACn), and a 26 mm versus 29 mm Evolut R were assessed after VIV implantation in 25 mm Mitroflow, Mosaic, and Magna Ease aortic surgical bioprostheses, at three implantation depths (+2 mm, ‐2 mm, and ‐6 mm). Results: The medium‐sized ACn had lower gradients compared to the small ACn when the THV was implanted high (+2 mm, or ‐2 mm). The 29 mm Evolut R had lower gradients compared to a 26 mm Evolut R for all implantation depths, except for a depth of ‐2 mm in the 25 mm Mitroflow. The medium ACn and 29 mm Evolut R had larger effective orifice areas compared to the small ACn and 26 mm Evolut R, respectively. Both Evolut R sizes had acceptable regurgitant fractions (<15%), while both ACn sizes were above the acceptable performance criteria (>15%), at all implantation depths. Conclusions: Use of a larger self‐expanding THV was associated with superior hydrodynamic performance if the THV was implanted high. Hydrodynamic testing can provide additional information to the VIV app to help guide VIV sizing.